Beyond technology: Towards sustainability through behavioral transitions - Miriam Bodenheimer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
The aim of this paper is to present a heterodox and heuristic model to analyze what we will call behavioral transitions to sustainability (BTS), using a combination of the Multi-Level Perspective (MLP), Dialectic Issue Lifecycles (DILC) and two behavioral models. With strong roots in science and technology studies, transition theories like the MLP approach have to date had a strong focus on technological transitions. However, in the context of sustainability transitions, which often require a change in behavior (Kemp, van Lente 2011), technological innovations are not always an effective solution (Lachman 2013). Particularly in the context of social sustainability, which so far has been neglected in the field of sustainability transitions, the focus of transitions needs to be first and foremost on changing attitudes, behaviors and the criteria used for decision-making, rather than on changing the technology employed, both on the part of producers and consumers (Lachman 2013). The focus in BTS is therefore on social innovations that involve changing existing behaviors to address specific sustainability issues.
urn:nbn:de:0011-n-4943438
Keywords: 330